Mitochondrial oxidative stress and cell death in podocytopathies - Zhu, Yu-Ting; Wan, Cheng; Lin, Jihong; Hammes, Hans-Peter; Zhang, Chun (Biomolecules, 2022)
Podocytopathies are kidney diseases that are driven by podocyte injury with proteinuria and proteinuria-related symptoms as the main clinical presentations. Albeit podocytopathies are the major contributors to end-stage kidney disease, the underlying molecular mechanisms of podocyte injury remain to be elucidated. Mitochondrial oxidative stress is associated with kidney diseases, and increasing evidence suggests that oxidative stress plays a vital role in the pathogenesis of podocytopathies. Accumulating evidence has placed mitochondrial oxidative stress in the focus of cell death research. Excessive generated reactive oxygen species over antioxidant defense under pathological conditions lead to oxidative damage to cellular components and regulate cell death in the podocyte. Conversely, exogenous antioxidants can protect podocyte from cell death. This review provides an overview of the role of mitochondrial oxidative stress in podocytopathies and discusses its role in the cell death of the podocyte, aiming to identify the novel targets to improve the treatment of patients with podocytopathies.